Primary Headache Disorders: Focus on Migraine - Bahra, Anish (Rev Pain, 2011)
Migraine is the most common disabling headache disorder. Most patients with disabling tension-type headache are likely to have migraine and accordingly respond to treatments efficacious in migraine. Individuals are genetically predisposed to experiencing recurrent migraine. Evidence supports migraine to be a primarily neural and not vascular mediated disorder. 1–2% of the population have chronic daily headache associated with acute-relief medication overuse; the majority are migraineurs. The presence of acute-relief medication overuse renders preventative medication less adequately efficacious.